ANALYSIS AND COMPARISION OF SRG AND DFIG FOR WIND GENERATION APPLICATION - Lenin, Dr. N. C.; Prathap, K. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2005)
Renewable energy is very important topic to be study to find new sources of energy to produce electricity. The main advantages of the renewable energy are available, clean, low cost, and continuous energy.The main objective of this paper is to document the comparative and absolute advantages and disadvantages of using Switched Reluctance Generator (SRG‟s) and Doubly Fed Induction Generator (DFIG‟s) in wind generation. The comparative study is based on the machine parameters like inductance, flux linkage, torque, output power, weight and cost. Performance analysis has been carried out using Finite Element Analysis (FEA). The predicted results show SRG‟S has the optimal choice for Wind Generation.